The Impact of Islamic Religious Education on Students’ Ramadan Fasting Practices: A Quantitative Study - Zubairi, Zubairi; Abnisa, Almaydza Pratama (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The article examines the relationship between learning Islamic Religious Education (PAI) (variable X) and students' practice of Ramadan fasting (variable Y). With a population of 216 students and a 10% margin of error using the Slovin formula, a sample size of 68 students was determined. Using a descriptive method and analysis with the product moment formula, the results showed that PAI learning has a significant positive effect on the practice of Ramadan fasting, with a count value of 148.843 greater than the table value of 1.997, a very strong correlation coefficient of 0.99, and an influence level of 1%, while the remaining 99% is influenced by other factors. The results suggest that students who receive high-quality PAI teaching tend to be more active and consistent in their fasting practices. Factors such as understanding of religious concepts, moral values, and social support from PAI teachers play a crucial role. The practical implications suggest the need to improve the quality of PAI learning in order to better support students in their Ramadan fasting practices.